Poverty and Environmental Degradation in Post-Conflict Aceh: A Socioeconomic Panel Data Study of 23 Regions - Juliansyah, Rollis; Salim, Jul Fahmi; Fitri, Hidayatul; Noviar, Helmi (Baileo: Jurnal Sosial Humaniora, 2025)
The decline in environmental quality has become a critical issue in various regions, including post-conflict Aceh, which is simultaneously grappling with poverty and environmental degradation. This study aims to analyze the relationship between poverty and environmental degradation within a socio-economic framework, focusing on 23 districts and municipalities in Aceh Province during the period of 2017–2022. Using panel data, the analysis employs the Fixed Effect Model (FEM) and Random Effect Model (REM) to test two main hypotheses regarding the influence of socio-economic variables on environmental quality and poverty levels. The findings indicate that poverty has a significant negative impact on environmental quality, whereas economic growth shows a positive influence in improving environmental conditions. These results underscore poverty as a key driver of environmental degradation and, conversely, highlight how poor environmental quality exacerbates poverty over the long term. The novelty of this research lies in its integrative approach, combining inter-regional panel data in a post-conflict setting with socio-economic statistical modeling—an approach rarely applied systematically in the context of Aceh. This study recommends the formulation of integrated policies that not only focus on poverty alleviation but also promote sustainable improvements in environmental quality. The implications of this research contribute to the advancement of social sciences and humanities, particularly in shaping inclusive development strategies grounded in ecological justice for vulnerable post-conflict regions.